Snapshot: eukaryotic ribosome biogenesis II - Hurt, Ed; Iwasa, Janet; Beckmann, Roland (Cell, 2024)
Ribosome production is essential for cell growth. Approximately 200 assembly factors drive this complicated pathway that starts in the nucleolus and ends in the cytoplasm. A large number of structural snapshots of the pre-60S pathway have revealed the principles behind large subunit synthesis. To view this SnapShot, open or download the PDF.
Gesehen am 21.10.2024